CORRELATION OF RISK FACTORS WITH SEVERITY OF DIABETIC RETINOPATHY - DURGA, VUYYURU SRI; PREMALATHA, GURIVINDAPALLI; PADMAVATHI, KATTOJU (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: Diabetic retinopathy (DR) is a major microvascular complication of diabetes. The purpose of the study is to correlate the risk factors such as duration of diabetes, hypertension, dyslipidemia, HbA1c, and high serum creatinine with severity of diabetic retinopathy. Methods: This is a hospital-based cross-sectional study conducted on 50 patients of diabetic retinopathy from March 2021 to August 2021. Best corrected visual acuity, slit lamp examination, and detailed fundus examination were done and grade of diabetic retinopathy was noted. The severity of diabetic retinopathy is correlated with duration of diabetes, HbA1c, serum cholesterol, BP, Hb%, and serum creatinine levels. Results: In our study, there was found to be a statistically significant association between duration of diabetes (p=0.03) and HbA1c levels (p=0.04) with severity of diabetic retinopathy whereas dyslipidemia (p=0.7), hypertension (p=0.8), high serum creatinine levels (p=0.4), and anemia (p=0.3) were shown to have no significant association with severity of diabetic retinopathy. Conclusion: In our study, the risk factors such as duration of diabetes and poor glycemic control have statistically significant association with severity of diabetic retinopathy and hypertension, dyslipidemia, anemia, and high serum creatinine have no significant association with severity of diabetic retinopathy. Thus, good glycemic control and regular screening for DR changes are the key to prevent progression of DR and to improve the quality of vision in diabetic patients.